Study of ill effects of air pollution due to automobiles on respiratory functions in traffic policemen - Dudhmal, Vandana; Kumar Nawal, Subodh (International Journal of Medical Research and Review, 2015)
Introduction: Every city is growing day by day and this growth is associated with enormous increase in vehicular traffic, emitting exhausts and polluting the atmosphere. vehicular population has been found to be an important cause of respiratory symptoms in city people.The adverse health effects and deterioration of pulmonary function from inhaling such particulate matters are well recognized. Although acute health effects have studied previously but chronic health effects related to outdoor traffic(automobiles) air population have not been evaluated that much. Material and Methods: A case control study was conducted in nanded city maharastra, A total of 120 subjects were studied in which 60 cases were smoker & nonsmoker traffic policemen and 60 controls were nonsmoker& not exposed to air pollution. Questionarre method used and respiratory functions (FVC, FEV1/FVC%) were recorded by using spirometer. The statistical analysis was done by using SPSS software and unpaired t test was applied for results. Results: The respiratory functions including forced vital capacity(FVC), forced expiratory volume in one second and forced vital capacity ratio as percentage (FEV1/FVC%) were reduced significantly in the traffic policemen than control group. Conclusion: Our study revealed that FVC had been significantly reduced in the traffic policemen suggesting restrictive pattern of lung disease.FEV1 and FEV1/FVC% were also significantly reduced in traffic police men suggesting obstructive lung disease, Thus our findings are suggestive of mixed type of lung disease in them. So from this study it can be concluded that the traffic policemen are in very high risk group for respiratory dysfunction and further measures to reduce automobile pollution has to be required or studies to prevent them from automobile pollution exposure should be done in urgent basis.